2010
DOI: 10.1111/j.1439-037x.2009.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Rice with System of Rice Intensification (SRI) and Conventional Management using Different Plant Spacings

Abstract: The System of Rice Intensification (SRI) reportedly enhances the yields of rice (Oryza sativa L.) through synergy among several agronomic management practices. This study was conducted to investigate the effects on rice plant characteristics and yield by comparing the plants grown with different methods of cultivation – SRI vs. recommended management practices (RMP) focusing on the impact of different plant spacings. Performance of individual hills was significantly improved with wider spacing compared with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 31 publications
(45 reference statements)
9
68
0
Order By: Relevance
“…Plant spacing affected the yield regardless of cultural practices; i.e., SRI and recommended practice. The highest yield was found at 20 by 20 cm spacing regardless of water management, and the yield of SRI (628 g m À2 ) was higher than that of conventional practice (448 g m À2 ) with 20 by 20 cm plant spacing (Thakur et al 2010a). Lin et al (2005) reported no significant difference in the yield of rice grown under shallow water with wetting and drying (SWD) among plant density of 7.5, 13.5 and 19.5 plants m…”
Section: Yields In Experimental Fieldsmentioning
confidence: 95%
See 4 more Smart Citations
“…Plant spacing affected the yield regardless of cultural practices; i.e., SRI and recommended practice. The highest yield was found at 20 by 20 cm spacing regardless of water management, and the yield of SRI (628 g m À2 ) was higher than that of conventional practice (448 g m À2 ) with 20 by 20 cm plant spacing (Thakur et al 2010a). Lin et al (2005) reported no significant difference in the yield of rice grown under shallow water with wetting and drying (SWD) among plant density of 7.5, 13.5 and 19.5 plants m…”
Section: Yields In Experimental Fieldsmentioning
confidence: 95%
“…Leaf area index (LAI) of rice plants planted at 13.5 plants m À2 was the highest among other plant densities evaluated (7.5 or 19.5 plants m À2 ) at 20 days after heading (Lin et al 2005). Although the largest leaf area per hill was found with wide plant spacing (30 by 30 cm) at flowering (Thakur et al 2010a), medium plant spacing (20 by 20 cm) recorded the highest LAI among treatments at 20 days after heading (Lin et al 2009;Thakur et al 2010a). The wider spacing between plants under SRI management leads to a more prolonged, open crop canopy (Stoop 2005).…”
Section: Plant Spacingmentioning
confidence: 95%
See 3 more Smart Citations